In vitro antibacterial, antibiofilm activities, and phytochemical properties of Posidonia oceanica (L.) Delile: An endemic Mediterranean seagrass - Ozbil, Ertugrul; Ilktac, Mehmet; Ogmen, Sultan; Isbilen, Ovgu; Ramirez, Jesus M. Duran; Gomez, Jana; Volkan, Ender (Cell Press, 2024)
In the antibiotic resistance era, utilizing understudied sources for novel antimicrobials or antivirulence agents can provide new advances against antimicrobial resistant pathogens. In this study, we aimed to investigate antibacterial and antibiofilm activities of Posidonia oceanica (L.) Delile against Enterococcus faecalis ATCC 29212, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922 and Klebsiella pneumoniae ATCC 700603 and several S. aureus clinical isolates obtained from medical devices, including patient urinary catheters and breast implant infections, with varying antibiotic recalcitrance profiles. The ethanolic and methanolic extracts from P. oceanica rhizome exhibited significant antibacterial activity against E. faecalis and S. aureus, , as well as drug resistant S. aureus clinical isolates. Furthermore, significant antibiofilm activity was observed against S. aureus and E. faecalis treated with ER, MR1, 1 , and MR2. 2 . P. oceanica extracts also exhibited synergistic antimicrobial activity with ciprofloxacin against E. faecalis, sensitizing E. faecalis to a lower ciprofloxacin concentration. Collectively, our data demonstrate the selective antibacterial and antibiofilm activity of the extracts of P. oceanica against Gram-positive bacteria and clinical isolates along with potentiation of current antibiotics, which suggests that P. oceanica can be further investigated as a potential source for novel therapeutic options in the treatment of drug resistant bacterial infections.
Keywords: Chemical-Composition; Antimicrobial Activity; Biological-Activity; Antioxidant